Chromosome-Level Genome Reveals the Origin of Neo-Y Chromosome in the Male Barred Knifejaw Oplegnathus fasciatus - Xiao, Yongshuang (2020)
The barred knifejaw, Oplegnathus fasciatus, is characterized by an X1X2Y system with a neo-Y chromosome for males. Here, a chromosome-level genome was assembled to investigate the origin of neo-Y chromosome to the male O. fasciatus. Twenty-three chromosomes corresponding to the male karyotypes were scaffolded to 762-Mb genome with a contig N50 length of 2.18 Mb. A large neo-Y chromosome (Ch9) in themaleO. fasciatus genomewas also assembled and exhibited high identity to those of the female chromosomes Ch8 and Ch10. Chromosome rearrangements events were detected in the neo-chromosome Ch9. Our results suggested that a centric fusion of acrocentric chromosomes Ch8 and Ch10 should be responsible for the formation of the X1X2Y system. The high-quality genome will not only provide a solid foundation for further sex-determining mechanism research in the X1X2Y system but also facilitate the artificial breeding aiming to improve the yield and disease resistance for Oplegnathus.